2004
DOI: 10.1073/pnas.0404161101
|View full text |Cite|
|
Sign up to set email alerts
|

Nitrosative stress linked to sporadic Parkinson's disease: S-nitrosylation of parkin regulates its E3 ubiquitin ligase activity

Abstract: Many hereditary and sporadic neurodegenerative disorders are characterized by the accumulation of aberrant proteins. In sporadic Parkinson's disease, representing the most prevalent movement disorder, oxidative and nitrosative stress are believed to contribute to disease pathogenesis, but the exact molecular basis for protein aggregation remains unclear. In the case of autosomal recessive-juvenile Parkinsonism, mutation in the E3 ubiquitin ligase protein parkin is linked to death of dopaminergic neurons. Here … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

14
469
3

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 488 publications
(486 citation statements)
references
References 27 publications
14
469
3
Order By: Relevance
“…46,47 Our group first identified the physiological relevance of S-nitrosylation by showing that NO and related RNS exert paradoxical effects via redox-based mechanisms -NO is neuroprotective via S-nitrosylation of NMDA receptors (as well as other subsequently discovered targets, including caspases), and yet can also be neurodestructive by formation of peroxynitrite (or, as later discovered, reaction with additional molecules such as parkin, PDI, GAPDH, and MMP-9) (Figure 1). 6,8,9,12,14,16,17,[19][20][21][22]48 Over the past decade, accumulating evidence has suggested that S-nitrosylation can regulate the biological activity of a great variety of proteins, in some ways akin to phosphorylation. 10,[49][50][51][52][53][54] Chemically, NO is often a good 'leaving group,' facilitating further oxidation of critical thiol to disulfide bonds among neighboring (vicinal) cysteine residues or, via reaction with ROS, to sulfenic (ÀSOH), sulfinic (ÀSO 2 H), or sulfonic (ÀSO 3 H) acid derivatization of the protein.…”
Section: Protein S-nitrosylation Affects Neuronal Survivalmentioning
confidence: 99%
See 4 more Smart Citations
“…46,47 Our group first identified the physiological relevance of S-nitrosylation by showing that NO and related RNS exert paradoxical effects via redox-based mechanisms -NO is neuroprotective via S-nitrosylation of NMDA receptors (as well as other subsequently discovered targets, including caspases), and yet can also be neurodestructive by formation of peroxynitrite (or, as later discovered, reaction with additional molecules such as parkin, PDI, GAPDH, and MMP-9) (Figure 1). 6,8,9,12,14,16,17,[19][20][21][22]48 Over the past decade, accumulating evidence has suggested that S-nitrosylation can regulate the biological activity of a great variety of proteins, in some ways akin to phosphorylation. 10,[49][50][51][52][53][54] Chemically, NO is often a good 'leaving group,' facilitating further oxidation of critical thiol to disulfide bonds among neighboring (vicinal) cysteine residues or, via reaction with ROS, to sulfenic (ÀSOH), sulfinic (ÀSO 2 H), or sulfonic (ÀSO 3 H) acid derivatization of the protein.…”
Section: Protein S-nitrosylation Affects Neuronal Survivalmentioning
confidence: 99%
“…10,[49][50][51][52][53][54] Chemically, NO is often a good 'leaving group,' facilitating further oxidation of critical thiol to disulfide bonds among neighboring (vicinal) cysteine residues or, via reaction with ROS, to sulfenic (ÀSOH), sulfinic (ÀSO 2 H), or sulfonic (ÀSO 3 H) acid derivatization of the protein. 19,20,22,55 Alternatively, S-nitrosylation may possibly produce a nitroxyl disulfide, in which the NO group is shared by close cysteine thiols. 19,56 Although the involvement of NO in neurodegeneration has been widely accepted, the chemical relationship between nitrosative stress and neuronal cell death has remained obscure.…”
Section: Protein S-nitrosylation Affects Neuronal Survivalmentioning
confidence: 99%
See 3 more Smart Citations